Penerapan model cooperative learning dalam peningkatan partisipasi dan hasil belajar siswa SMP dalam pembelajaran IPS Geografi - Lalu Abdul Masyaekh (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
Classroom Action Research (CAR) aims to increase student participation in teaching and learning activities and student learning outcomes with the use of cooperative learning models. The results showed that in the first cycle the average was 60.5; in the second cycle 64.38; and in the third cycle it reaches 70.38. It was concluded that the learning process with cooperative learning can increase student participation and learning outcomes.